What’s Weight Got to Do With It? Mental Health Trainees’ Perceptions of a Client With Anorexia Nervosa Symptoms - Veillette, Laurie A. S.; Serrano, Jose Martinez; Brochu, Paula M. (Frontiers in Psychology, 2018)
This study examined the effect of client body mass index (BMI) on diagnostic impressions and perceptions of mental health trainees. Participants read a vignette of a mock female client presenting for treatment with symptoms of anorexia nervosa. Participants were randomly assigned to one of three conditions in which the client was described as “underweight,” “normal weight,” or “overweight.” Results revealed that participants assigned to the “underweight” condition diagnosed the client with anorexia nervosa or atypical anorexia nervosa more frequently than participants assigned to the “overweight” or “normal weight” conditions. There was no difference based on client BMI when the more general diagnosis of other specified feeding or eating disorder (OSFED; previously known as eating disorder not otherwise specified [EDNOS]) was included, however. Participants in the “overweight” and “normal weight” conditions recommended fewer therapy sessions for the client than participants in the “underweight” condition. Furthermore, participants more strongly endorsed weight-based stereotypes to describe the client when she was “overweight” than “normal weight” or “underweight.” Contrary to hypotheses, however, participants reported moderately positive attitudes toward treating the client regardless of BMI. These preliminary findings support initiatives aimed at providing training on weight stigma and eating disorders to mental health professionals.